Dynamic Quality-of-Service Management Under Software-Defined Networking Architectures - Ana Rita de Almeida Martinho (2021)
The Internet is facing new challenges emerging from new trends in Information and Communication Technologies (ICT) for example, cloud services, Big Data, increased mobile usage etc. Traditional IP networks rely in two design principles that, despite serving as an effective solution in the last decades, have become deprecated and not well fit for the new challenges. First, the control and data plane are tightly embedded in the networking devices and second, the structure is highly decentralized with no centralized point of management. This static and rigid architecture leaves no space for innovation with a consequence lack of scalability. Also, it leads to high management and operation costs. The SDN paradigm provides a more dynamic, manageable, cost-effective and adaptable architecture that is ready for the dynamic nature of today's applications. The goal of this thesis is a novel SDN-enabled solution that provides dynamic Quality of Service management for real-time and multimedia applications. This solution will be tested and implemented over a real, not-simulated testbed, composed by OpenFlow-enabled devices, the ONOS SDN controller and client terminals that produced/consume data streams. Furthermore, it is also expected to characterize and evaluate the benefits of the SDN-based solution against a traditional usage of the network (non-SDN).